Condition of the humoral link of immune system at patients with endometrial cancer - A. V. Efremov; N. A. Matveevskij; A. N. Trunov; I. D. Safronov (Опухоли женской репродуктивной системы, 2014)
Examine changes in the parameters reflecting the activation of humoral immune system, the severity of the destructive processesand autoimmune reactions in patients with endometrial cancer . The findings suggest that the significance of activation of autoimmune reac tions and destructive processes in pathogenetic mechanisms of development of malignant tumors of the corpus uteri.